Migration studies and toxicity evaluation of cyclic polyesters oligomers from food packaging adhesives. (1st May 2020) - Ubeda, Sara; Aznar, Margarita; Rosenmai, Anna Kjerstine; Vinggaard, Anne Marie; Nerín, Cristina
Highlights: Two cyclic esters present in polyurethane adhesive were evaluated. Migration assays of 20 multilayer packaging samples were performed. Oligomers migration values of most samples exceeded 10 ng g −1. Bioaccessibility studies showed a decrease of oligomers after digestions. Only a weak androgen receptor antagonism was identified in endocrine test. Abstract: Multilayer materials used in food packaging are commonly manufactured with a polyurethane adhesive layer in its structure that may contain cyclic esters oligomers as potential migrants. However, little is known about their toxicity. In this work, two cyclic esters of polyurethane are evaluated in migration from 20 multilayer packaging samples. They were composed by adipic acid (AA), diethylene glycol (DEG) and isophthalic acid (IPA) and their structure was AA-DEG and AA-DEG-IPA-DEG. The concentration of these compounds in migration exceeded the maximum level established by Regulation EU/10/2011 (10 ng g −1 ). Bioaccessibility of both compounds was evaluated by studying gastric and intestinal digestion. The studies showed that the concentration of the compounds decreased during digestion and that their hydrolysed molecules increased. Furthermore, endocrine activity in vitro assays were performed. A weak androgen receptor antagonism was identified, whereas no arylhydrocarbon receptor activity or binding to the thyroid hormone transport protein was found.